Study the sentences in the children's story books of Ay Nounoy Publishing House in Luang Prabang - Amphaithip, Khampha; Phommaseng , Sisoury; Phommachan, Souphanith (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of this study was to analyze the sentence structures in the children's story books of Ay Nounoy Publishing House in Luang Prabang. In the study, 10 of the children's story books were analyzed based on the concept of Phoumy Vongvichit before drawing to the summary and discussion of results in a descriptive way. The result revealed that the sentence structure that consists of two parts (subject, verb (intransitive)) includes direct, complete, and common sentences, while the sentence structure that consists of three parts (subject, verb (transitive), and object) includes: direct, indirect, affirmative, complex sentences, common, and compound sentences. The subjects of the sentences are mostly in the form of nouns or pronouns. The objects of the sentences are also seen in the forms of phrases, nouns, and clauses. In addition, there are prepositions, conjunctions, and adjectives that help modify the sentences. In summary, it can be said that the sentences in the children's story books of Ay Nounoy Publishing House in Luang Prabang are simple with a variety of structures, and the vocabulary employed in the sentences are the original Lao root words that are easy for children to memorize and understand.